Prevalence and antimicrobial resistance of Escherichia coli and Salmonella spp. in animal feed in Colombia - Rocío Paredes; Monica Damme; Jazmin Mantilla; Luis Ricardo Castellanos; Viviana Clavijo; Yamile Celis; Kedar Mehta; Ajay Kumar; Ana Patiño; Kathiresan Jeyashree (Pan American Health Organization, 2023)
Objective. To determine the prevalence and antimicrobial resistance of Escherichia coli and Salmonella spp. in animal feed samples collected between 2018 and 2021 in Colombia. Methods. This was a laboratory-based cross-sectional study using routine data from the program for inspection, surveillance, and control of animal feed at the Colombian Agriculture Institute. Samples of animal feed for swine, poultry, canine, feline, leporine, piscine, and equine species were processed for detection of E. coli and Salmonella spp. using enrichment and selective culture methods. Isolates were tested for antimicrobial susceptibility using an automated microdilution method. Results. Of 1 748 animal feed samples analyzed, 83 (4.7%) were positive for E. coli and 66 (3.8%) for Salmonella spp. The presence of E. coli and Salmonella spp. was highest in feed for poultry (6.4% and 5.5%) and swine (6.1% and 4.3%). Antimicrobial resistance testing was performed in 27 (33%) E. coli isolates and 26 (39%) Salmonella isolates. Among E. coli, resistance was most frequently observed to ampicillin (44.5%) followed by cefazolin (33.3%), ciprofloxacin (29.6%), ampicillin/sulbactam (26%), and ceftriaxone (11.1%). The highest resistance levels in Salmonella spp. isolates were against cefazolin (7.7%) and piperacillin/tazobactam (7.7%). Conclusions. This is the first study from Colombia reporting on the prevalence and antimicrobial resistance of E. coli and Salmonella spp. in animal feed samples. Its results establish a baseline over a wide geographical distribution in Colombia. It highlights the need to integrate antimicrobial resistance surveillance in animal feed due to the emergence of resistant bacteria in this important stage of the supply chain.